The methodology for evaluation and predicting of clothing comfort for functional apparel - LADISLAV, NAGY; MARIE, KOLDINSKÁ; ANTONÍN, HAVELKA; SOŇA, JANDOVÁ (Industria textilă (Bucharest, Romania : 1994), 2018)
The aim of this study was testing the first layer of clothing. It can be used separately, or together with other layers of textiles in the sandwich structure of clothing. As this layer is in direct contact with the skin, the evaluation does not focus only on its thermo physiological properties, but also on sensory perception of the fabric. The main purpose of this layer is to transport heat and moisture from the skin to surface, or to the other layers. One way of assessing the physiological comfort of the garment is testing garments under defined conditions and standards in a laboratory. For testing, T-shirts made from 100 percent natural fibres, chemical fibres, and also mixed fibres for the comparison were chosen. Experimental work was carried out in the following two steps of laboratory testing: measurement of selected utility properties in the Laboratory of Physiological Comfort, and the measurement degree of Total Hand Value in the Kawabata Evaluation System. For the prediction of clothing comfort and the garment performance quick assessment, a simple equation for the comparison of the selected set of T-shirts was also created.